Crusted (Norwegian) scabies due to topical corticosteroid abuse. - Chirag, N.; Shilpashree, P. (European Journal of Pediatric Dermatology, 2022)
Norwegian scabies is an entity that is mainly observed in patients with immunodeficiency, such as that caused by AIDS, leukemia, human T-lymphotrophic virus-1 infection and systemic immunosuppressive therapies, or in patients with neuropsychiatric disorders, such as senile dementia, sensory neuropathy, Down syndrome and other mental retardation or even in those with a debilitating disease such as malnutrition (1, 4-6). Unlike common scabies, Norwegian scabies is characterized by the presence of thousands or even millions of viable mites, due to a deficient immunological response or reduced mechanical removal of the mites, due to mental retardation or decreased skin sensitivity; this form is therefore extremely contagious (...).